A sieve that does hold a little water – gambling advertising and protection of the vulnerable in the UK. (23rd July 2018) - Hörnle, Julia; Carran, Malgorzata A
Abstract: The internet, social media and online profiling have fundamentally changed advertising, and the regulation of gambling advertising has not yet managed to address the challenges and opportunities arising from this technological shift. Furthermore, the regulation of gambling does not take into account sufficiently the needs of children and vulnerable persons. We review the empirical research on the impact of gambling advertising and show how regulatory standards firmly adhere to the transmission theory of communication that prioritises the communicative intent of the advertiser over how the advertising message is received by or impacts on vulnerable people. This article reviews the law on gambling advertising and argues that for gambling, the restrictions imposed by the largely co-regulatory system only have limited effect. We compare the regulation of gambling advertising, by way of analogy, to a sieve that holds only a little water, and make recommendations for legal reform.